The last of the prince bishops: William Van Mildert and the High Church movement of the early nineteenth century - Varley, E. (Cambridge University Press, 1992)
This study examines the significance of the influential High Church 'Hackney Phalanx' at the beginning of the nineteenth century, and opens up a little-explored area of Anglican history. Drawing extensively upon original correspondence, Elizabeth Varley reconstructs the work of the Hackney Phalanx and their defence of traditional Anglican ascendancy against the forces of political and religious reform during the final crisis of the English confessional state. The study focuses upon William Van Mildert, Bishop of Durham from 1826–36, and shows that, while Van Mildert's influence as 'Prince Bishop' bore little resemblance to his medieval forebears, he made effective use of it to cause considerable irritation to the Whig establishment of the day, local and national. Varley brings skilfully to life many of the tensions of that time - political and ecclesiastical - which culminated in the Catholic Emancipation Act of 1829 and the passing of the Parliamentary Reform Bill in 1832.